The Implementation of Education Character at Salafiyah Islamic Boarding Schools in the Modern Era Study at Darul Mustofa Tempuran Islamic Boarding School - Ayu Wahyuni; Ahmad Mubaroq; Ahmad Nur Qosim Husen (CV. Creative Tugu Pena, 2021)
This study aims to describe and analyze the implementation of character education at Pondok Pesantren Salafiyah Darul Mustofa in response to the challenges of the modern era. Amidst the waves of globalization and technological advancement that influence the values of younger generations, traditional Islamic boarding schools (pesantren salafiyah) remain steadfast in upholding education based on classical Islamic values. This research employed a qualitative approach with a case study method. Data were collected through participant observation, in-depth interviews with caregivers, teachers, and students, as well as documentation of pesantren activities. The findings reveal that Pondok Pesantren Darul Mustofa implements character education through four main aspects: (1) Strengthening religious values, achieved through the habituation of worship practices such as congregational prayers, night prayers (qiyamul lail), voluntary fasting, the study of classical Islamic texts on ethics and spirituality, as well as daily dhikr and post-prayer recitations; (2) Instilling discipline and responsibility, through a structured daily schedule, assigned duties such as cleaning and night guards, and an educational disciplinary system; (3) Habituating manners and ethics, by cultivating respectful behavior toward teachers, proper etiquette during study, and politeness in social interactions; and (4) Fostering social responsibility and leadership, through student-led organizations, community service, group deliberations, and public speaking training. This study contributes theoretically to the development of a pesantren-based character education model and provides practical implications for educational institutions and policymakers. Future research is recommended to conduct comparative or longitudinal studies to assess the sustainability of these character values in the lives of pesantren alumni. Keywords: Character Education, Salafiyah Pesantren, Modern Era, Religiosity, Manners, Leadership